Alternative livestock feed from fermented banana peel / Muhammad Afiq Jais, Nurul’ Ain Jamion and Hasratul Nadiah Mohd Rashid - Jais, Muhammad Afiq; Jamion, Nurul’ Ain; Mohd Rashid, Hasratul Nadiah (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Silage is one of the preservation methods for animal feed during periods of feed shortages by fermentation method. It has a potential to be an alternative livestock feed resources such as cattle and goat. The silage prepared from banana peel is suitable since banana is one of the native plants in Malaysia. This study is aimed to prepare an alternative livestock feed from banana peel which was obtained around Kuala Pilah area, Negeri Sembilan was ensiled in two different drums for 21 days. Samples from each drum were taken for analysis of physical observation (odour and colour), dry matter (DM), and ash contents. Other parameters such as the temperature, pH value, volatile fatty acid (VFA), and water soluble carbohydrates (WSC) were also being conducted. Results obtained show the colour of silage was light green and the odour was mild and sour milk smell. For pH analysis which was measured after the ensiling process, was obtained at 3.96. The low pH value shows high-quality fermentation ranged from 3.5 - 4.5. The DM and ash contents were 45.67 % and 5.21 % respectively as these value were compatible for livestock feed. In conclusion, ensiling by-product like banana peel has good potential as it simple, low-cost and also produces a high-quality feed to livestock.